Quantitative research on the sense of place: visualizing literature through systematic reviews and bibliometric analysis - Ma, Yue; Mohd Ariffin, Noor Fazamimah; Abdul Aziz, Faziawati; He, Xiao; Liu, Yuanyuan; Zhao, Jing (Universiti Putra Malaysia Press, 2025)
The concept of a sense of place, involving the emotional and cognitive connections between individuals and specific locations, has long been a focal point of research in the social sciences. To delve deeper into this topic, this study employed VOS viewer software to conduct PRISMA process screening of an initial pool of 675 articles from the Scopus database, eventually selecting 249 for in-depth systematic literature review and bibliometric analysis. co-authorship, co-occurrence, citation, bibliographic coupling, and term, to elucidate the core themes, key scholars, and development trends in this field. The findings indicate a shift in the sense of place research from traditional paradigms toward a new paradigm that integrates diverse perspectives and interdisciplinary approaches. Particularly in the last five years, “tourism” and “tourist” have emerged as core exploration themes, economic development imperatives and the demands of community or destination management. This suggests that sense of place research is actively adapting to new research paradigms, focusing on developing the tourism industry and community management needs in the face of globalization and economic development challenges. This study provides a comprehensive perspective through a systematic literature review and bibliometric analysis, offering valuable insights into this research field’s current status and future developments.